The Spirit of Liberation : Jürgen Moltmann's Trinitarian Pneumatology - Yoo, Tae Wha, (Studies in Reformed Theology;, 2003)
With this study on Moltmann's pneumoatology the author recently obtained the doctor's degree from the Faculty of Theology of the Free University in Amsterdam. First of all, the book provides us with a thorough evaluation of the role the Holy Spirit plays in the theology of Jürgen Moltmann in its subsequent phases. The author's conclusion is that despite all differences there is one contstant factor: the Spirit is always connected with freedom. The Holy Spirit, according to Moltmann, is a liberating power. Because the author is eager to place Moltmann's pneumatology repeatedly in the context of his theology as a whole and of its developments, this book offers - and that is a second quality - an outstanding insight in the whole of Moltmann's theology and its development throughout the years.